EFFECT OF VARIOUS PHYSICOCHEMICAL PARAMETERS ON SIDEROPHORE PRODUCTION BY MARINE Pseudomonas aeruginosa MGPB31 (Applied Biological Research, 2024)
Siderophores are low molecular weight compounds secreted by bacteria that  bind ferric iron with extremely high affinity. The siderophores help bacteria to  meet their iron needs under stress conditions as these compounds help in the  transport and storage of soluble form of iron in cells. In current study, we report  the effect of various physicochemical parameters that influence siderophore  production in marine Pseudomonas aeruginosa MGPB31. Siderophore  production was assayed using Chrome Azurol S (CAS) shuttle assay. The  maximum siderophore production (56% SU) was obtained in minimal M9  medium after 72 h incubation, followed by succinate medium (52% SU) and  King’s medium (51% SU). The M9 medium was then modified by replacing its  carbon, nitrogen and phosphate source. Enhanced siderophore production was  observed in modified medium comprising of glycerol (70% SU), tri ammonium  citrate (67% SU) and KH2PO4 (64% SU). The medium supplemented with iron  exhibited a significant reduction in siderophore production. The effect of  physical parameters like temperature, pH and agitation on siderophore  production revealed that the isolate exhibited maximum siderophore production  under static conditions in modified M9 medium devoid of iron at 25 ± 2°C and  neutral pH. The enhanced siderophore production obtained by marine P. aeruginosa MGPB31 indicates its further applicability in fields of industry  agriculture and environment.
Keywords: CAS; glycerol; iron, agitation; MM9 medium; siderophore